2019
DOI: 10.1139/cjb-2018-0207
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling seed dormancy and germination response of Brachypodium hybridum growing in the hot arid mountains of the Arabian Desert

Abstract: Seed dormancy and germination have been studied in the genetic model Brachypodium species complex in cooler, moist higher latitudes. Studying environmental factors in arid mountains affecting dormancy and germination in Brachypodium complex could determine the factors controlling these processes. This study assesses the impacts of temperature during seed maturation, seed after-ripening, drought, photoperiod, and thermoperiod on final germination and germination rate index of B. hybridum in the Arabian Desert. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Conversely, germination was observed as significantly lower in darkness and other light settings (white light, R: FR ratios of 0.25 and 0.87) (Figure 5). In a previous study, we found that germination of husked grains had a similar response to different light settings; i.e., they germinated more under red-rich light and less in darkness [20]. In dehusked-demembraned grains, however, there was no significant difference in the final germination triggered under different light qualities (Figure 5).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Conversely, germination was observed as significantly lower in darkness and other light settings (white light, R: FR ratios of 0.25 and 0.87) (Figure 5). In a previous study, we found that germination of husked grains had a similar response to different light settings; i.e., they germinated more under red-rich light and less in darkness [20]. In dehusked-demembraned grains, however, there was no significant difference in the final germination triggered under different light qualities (Figure 5).…”
Section: Discussionmentioning
confidence: 69%
“…The inconsistency observed in the role of husks on germination in B. distachyon and B. hybridum respectively could be attributed to the maternal environment during seed development and maturation. Whereas B. distachyon is a summer annual in temperate climate at the northern latitudes [12], B. hybridum is a winter annual in the arid hot climate of the Arabian desert [20]. Environmental conditions can affect the chemical compositions of different parts of grasses, such as Lolium perenne [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germination of spore is defined as the set of mechanisms occurring in the dormant spore that culminates with the growth of cells to form a sporeling able to be established in the substrate (Gabriel y Galán et al 2015; Steinbrecher and Leubner-Metzger 2017; Yan and . Spore germination can be easily detected by observing signs of the emergence of particular organs such as radicle, protonema, filament or rhizoid (Suo et al 2015;Penfield 2017;Elgabra et al 2019). Spores of C. barometz are trilete, tri-radially symmetrical, non-chlorophyllous, and golden-yellow with a perine.…”
Section: Spore Germination and Early Gametophyte Development Stages Omentioning
confidence: 99%